2007
DOI: 10.1111/j.1365-2966.2006.11148.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic survey for infrared star clusters with  b  < 20  using 2MASS

Abstract: We used star density maps obtained from the Two-Micron All-Sky Survey (2MASS) to obtain a sample of star clusters in the entire Galactic Plane with |b| < 20 • . A total of 1788 star cluster candidates are identified in this survey. Among those are 681 previously known open clusters and 86 globular clusters. A statistical analysis indicates that our sample of 1021 new cluster candidates has a contamination of about 50 per cent. Star cluster parameters are obtained by fitting a King profile to the star density. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
326
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(355 citation statements)
references
References 17 publications
27
326
0
1
Order By: Relevance
“…Robitaille et al (2008), Evans et al (2009), andGutermuth et al (2010) used Spitzer data to classify > 13 × 10 3 YSOs. Borissova et al (2011) discovered 96 candidate clusters 2 in the VVV survey (Minniti et al 2010), while Mercer et al (2005) identified 92 star clusters via GLIMPSE data (see also Froebrich et al 2007;Kronberger et al 2006). Those infrared surveys resolved numerous individual cluster stars, and in many instances confirmed existing evidence of star formation put forth by low-resolution surveys (e.g., IRAS and maser observations, Avedisova 2002).…”
Section: Introductionmentioning
confidence: 84%
“…Robitaille et al (2008), Evans et al (2009), andGutermuth et al (2010) used Spitzer data to classify > 13 × 10 3 YSOs. Borissova et al (2011) discovered 96 candidate clusters 2 in the VVV survey (Minniti et al 2010), while Mercer et al (2005) identified 92 star clusters via GLIMPSE data (see also Froebrich et al 2007;Kronberger et al 2006). Those infrared surveys resolved numerous individual cluster stars, and in many instances confirmed existing evidence of star formation put forth by low-resolution surveys (e.g., IRAS and maser observations, Avedisova 2002).…”
Section: Introductionmentioning
confidence: 84%
“…Majaess (2013) has also made a significant contribution on young clusters (see also, Bica et al 2003a,b;Lada & Lada 2003;Mercer et al 2005;Froebrich, Scholz & Raftery 2007;Borissova et al 2011;Solin, Haikala & Ukkonen 2014).…”
Section: Introductionmentioning
confidence: 94%
“…This increases the number of near-infrared cluster candidates to 2404. Froebrich et al (2007) estimate that the spurious contamination rate (false positives) for new and unconfirmed infrared clusters from these catalogs may be as high as 50%. However, the probability of yielding bona fide stellar clusters in our sample is high (as in Borissova et al 2011) and we expect minimal contamination from spurious detections.…”
Section: Cluster Search and Methods Of Analysismentioning
confidence: 99%